Stocks Allocation in Portfolio Selection using Fuzzy Soft Set - Harode, Shraddha; Jha, Manoj; Das, Sujoy; Srivastava, Namita (International Journal of Engineering and Technology, 2018)
Return and risk are uncertain parameters for stock market. Fuzzy Soft Set is a suitable approach to handle the uncertaintiesvagueness and/or imprecisionof the market position and permits the data representation viably. The primary focus of paper is to construct the diversified portfolio of the stocks with the help of Fuzzy Soft Set (FSS) model.HereinFSS model is used for ranking the stocks viadecision making factor (DMF) and decision ranking factor (DRF).On the basis of this ranking7 stocks are picked up out of 30 stocks for construction of optimal portfolio. To solve optimization problem, Genetic Algorithm isused for stocks allocation of the optimal portfolio. The data set analysedin this model is taken from Bombay Stock Exchange (BSE) Mumbai, India and a real application are given in order to show the potentiality of the approachÂ Â Â